Adipose Tissue Stimulates Bone Growth in Prepubertal Children - Emma Clark; Andy Ness; Jonathan H. Tobias (2006)
Fat mass represents a positive influence on bone mass in adults, independently of other factors such as lean mass, but whether a similar action occurs in children is unclear.